Clinical Presentation of Pediatric Myocarditis in Taiwan - Hsiang-Ju Hsiao; Shao-Hsuan Hsia; Chang-Teng Wu; Jainn-Jim Lin; Hung-Tao Chung; Mao-Sheng Hwang; Wu-Jen Su; Yu-Sheng Chang (Pediatrics and Neonatology, 2011)
The purposes of this study were to characterize the symptoms and signs of children with myocarditis at the time of presentation to the hospital and to identify the predictors of death. Methods: This was a 5-year retrospective study in a tertiary hospital. We collected demographic data and clinical symptoms and signs when children with myocarditis presented at the hospital. The outcome for patient was classified as either survival or death, and the predictors of death were identified. Results: Over the 5-year period, 27 children (14 boys and 13 girls) met the definition of clinical myocarditis. The mean age of the myocarditis patients was 9.1±5.1 years (range, 0.08–17.9 years), and the maximum age was 10–12 years. The most common presentation was gastrointestinal symptoms. We used extracorporeal membrane oxygenation on nine (33%) children, and pacemaker was implanted in eight (30%). Six (22%) children died in this study, and only one of them was younger than 6 years. The poor prognosis predictors were gastrointestinal symptoms, hepatomegaly, and hypotension. Conclusions: Pediatric myocarditis presents primarily with gastrointestinal symptoms in Taiwan. Careful check of heart rhythm may provide a useful objective marker of myocarditis. The predictors of a poor prognosis were gastrointestinal symptoms, hepatomegaly, and hypotension.